ANALISIS LAJU KOROSI ELEKTRODE BAHAN Cu - Zn DENGAN METODE SACRIFICIAL ANODE PADA SISTEM ENERGI LISTRIK ALTERNATIF BERBASIS AIR LAUT - Gurum Ahmad Pauzi; Latifah Kamalia; Sri Wahyu Suciati (Jurnal Teori dan Aplikasi Fisika, 2018)
In this study, the addition of aluminum (Al) and magnesium (Mg) at the zinc (Zn) electrode as the sacrifice anode in an alternative sea-based electrical energy system was carried out. The sacrifice anode method is used as a way to prevent the corrosion of Zn electrodes. There are 3 types of electrode treatments, namely Cu-Zn, Cu-ZnAl, and Cu-ZnMg. The tool is designed to have 20 cells arranged in series and given a load of 3 Watt LED lights. Tool testing is carried out for 72 hours with electrolyte replacement every 24 hours. The measurement results showed that the Cu-ZnMg electrode produced the highest power output compared to the Cu-Zn and Cu-ZnAl electrodes. The maximum value of power from the Cu-ZnMg electrode is 125.71 mW while the electrodes of Cu-Zn and Cu-ZnAl have maximum power values of 49.49 mW and 52.48 mW respectively. The value of the intensity of the light generated from the instrument shows that the greater the power released, the higher the intensity of light. The lowest corrosion rate was generated by the Cu-ZnMg electrode of 0.079 mm/year after 72 hours of testing. This shows that the addition of sacrificial anode metal with a higher potential electrode value can produce higher and longer electrical energy and a lower corrosion rate